STRATEGI KEPALA SEKOLAH DALAM MANAJEMEN WAKTU KEGIATAN BELAJAR PADA PROGRAM FULL DAY SCHOOL DI SMA NEGERI 8 MUARO JAMBI - Lisa Ramayanti; Mohamad Muspawi; Linardo Pratama (STKIP Pesisir Selatan, 2026)
This study aims to determine the principal's strategy in managing learning time in the full-day school program at SMA Negeri 8 Muaro Jambi. This study uses a qualitative approach with a case study research type. Data were obtained through interviews, observation, and documentation. Research informants consisted of the principal, vice principal for curriculum, teachers, and students. The results of the study indicate that the principal's strategy in managing learning time is carried out through three stages: planning, implementation, and monitoring/evaluation. In the planning stage, the preparation of learning duration refers to government regulations and student conditions. Subject placement is based on student concentration levels from morning to afternoon. The balance of academic and non-academic activities is through clear coordination and division of tasks. In the implementation stage, learning activities are carried out according to the established schedule, taking into account the effectiveness of the schedule and student involvement. In the monitoring/evaluation stage, the school holds a meeting to assess the implementation of the schedule and make improvements to any obstacles found. The novelty of this study lies in the focus of the study on the principal's strategy in managing learning time in the full-day school program at SMA Negeri 8 Muaro Jambi.